2023
DOI: 10.4178/epih.e2023020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an air quality warning system for vulnerable and susceptible individuals in Korea: an interrupted time series analysis

Abstract: Objectives: This study was conducted to elucidate the effects of an air quality warning system (AQWS) implemented in January 2015 in Korea by analyzing changes in the incidence and exacerbation rates of environmental diseases.Methods: Data from patients with environmental diseases were extracted from the National Health Insurance Service-National Sample Cohort database from 2010 to 2019, and data on environmental risk factors were acquired from the AirKorea database. Patient and meteorological data were linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Park et al 34 investigated the incidence and exacerbation of CVDs before and after the implementation of a text-message-based Air Quality Warning System in Korea in 2015. The authors found that the system’s implementation was associated with a reduction in incident CVD (relative risk, 0.66 [95% CI, 0.47–0.92]).…”
Section: Personal Strategies To Protect the Cardiovascular System Fro...mentioning
confidence: 99%
“…Park et al 34 investigated the incidence and exacerbation of CVDs before and after the implementation of a text-message-based Air Quality Warning System in Korea in 2015. The authors found that the system’s implementation was associated with a reduction in incident CVD (relative risk, 0.66 [95% CI, 0.47–0.92]).…”
Section: Personal Strategies To Protect the Cardiovascular System Fro...mentioning
confidence: 99%